An Analysis of Subtitle Translation Strategies in Miss Peregrine's Home for Peculiar Children - Joanna Felicia Andrianto (CV Insan Kreasi Media, 2026)
This study examines subtitle translation strategies in the official Indonesian subtitles of Miss Peregrine's Home for Peculiar Children (2016), directed by Tim Burton. Guided by Pedersen's (2011) seven-strategy typological framework, the study employs a descriptive qualitative approach with content analysis as its primary method. A corpus of 44 purposively selected subtitle segments, drawn from Blu-ray rip files and cross-verified against official subtitles on Netflix and Disney+ Hotstar, was analyzed across four fantasy genre components: invented neologisms, world-building references, meaningful character names, and fantasy idioms and metaphors. Findings reveal that only three strategies were present in the corpus. Retention was dominant (68.2%), consistently applied to fantasy-specific neologisms such as ymbryne, hollowgast, and peculiar. Specification accounted for 22.7% of cases, used exclusively for the world-building term